A computational workflow for rupture‐to‐structural‐response simulation and its application to Istanbul. (28th October 2020) - Zhang, Wenyang; Restrepo, Doriam; Crempien, Jorge G.F.; Erkmen, Bulent; Taborda, Ricardo; Kurtulus, Asli; Taciroglu, Ertugrul
Abstract: Scenario‐based earthquake simulations at regional scales hold the promise in advancing the state‐of‐the‐art in seismic risk assessment studies. In this study, a computational workflow is presented that combines (i) a broadband Green's function‐based fault‐rupture and ground motion simulation—herein carried out using the "UCSB (University of California at Santa Barbara) method", (ii) a three‐dimensional physics‐based regional‐scale wave propagation simulation that is resolved at f max = 11.2  Hz, and (iii) a local soil‐foundation‐structure finite element analysis model. These models are interfaced with each other using the domain reduction method. The innermost local model—implemented in ABAQUS—is additionally enveloped with perfectly matched layer boundaries that absorb outbound waves scattered by the structures contained within it. The intermediate wave propagation simulation is carried out using Hercules, which is an explicit time‐stepping finite element code that is developed and licensed by the CMU‐QUAKE group. The devised workflow is applied to a 80 × 40 × 40  km 3 region on the European side of Istanbul, which was modeled using detailed soil stratigraphy data and realistic fault rupture properties, which are available from prior microzonation surveys and earthquake scenario studies. The innermost local model comprises a chevron‐braced steel frame building supported by a shallow foundation slab, which, in turn, rests atop a three‐dimensional soil domain. To demonstrate the utility of the workflow, results obtained using various simplified soil‐structure interaction analysis techniques are compared with those from the detailed direct model. While the aforementioned demonstration has a limited scope, the devised workflow can be used in a multitude of ways, for example, to examine the effects of shallow‐layer soil nonlinearities and surface topography, to devise site‐ and structure‐specific seismic fragilities, and for calibrating regional loss models, to name a few.